Hardware and Software Development of Mobile Electrocardiogram (ECG) System - Iwan Tutuka Pambudi; Rony Febryanto; Harry Prihanto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
This paper proposes a mobile electrocardiogram (ECG) system based on microcontroller technology. Aportable device was developed to acquire ECG signals and transmit them using GSM network. ECG is anelectrical recording of the heart which is used by phycisian in regular medicine practice to monitore thecondition of the heart of the patient and to detect abnormalities because of heart disease. Using this mobile ecgsystem patients in a rural or remote area can be telemonitored. And this system is an ongoing project thereforeimprovements are still required to enhance the system performance.Keywords: Electrocardiography, portable device, telemonitoring,